Criminal Liability in The Perspective of Corporations' Crimes - Endang Rusyana; Januar Agung Saputera (Jurnal Indonesia Sosial Sains, 2024)
This study explores corporate criminal liability in the context of Indonesia’s legal system, focusing on the complexities arising from corporate crime enforcement. Corporate crime, involving illegal activities by business entities for profit, requires a distinct legal approach since corporations as legal subjects cannot be held accountable in the same way as individuals. The research reviews various laws, including the Limited Liability Company Law and the Anti-Corruption Law, examining the challenges in applying these regulations, particularly in proving corporate intent and responsibility. Using a normative legal research method, the study analyzes legal documents and case studies to understand how Indonesia handles corporate crime. The findings reveal significant enforcement difficulties due to overlapping legal frameworks, gaps in corporate oversight, and insufficient legal mechanisms. International comparisons, such as the U.S. doctrine of "vicarious liability," highlight the potential for stronger corporate governance in Indonesia. The study concludes that harmonizing regulations and strengthening law enforcement are critical to improving corporate criminal liability in Indonesia, with recommendations for better compliance systems and enhanced international cooperation.